Decoration, Deviation, and the Selected Edition: Some Poems of Lionel Johnson (1912) - Jeremy Valentine Freeman (Cahiers Victoriens et Edouardiens)
With the 1912 publication by Elkin Mathews of a selection from Lionel Johnson’s posthumous works titled Some Poems of Lionel Johnson, the complex representation, marketing, and intellectual inheritance of Victorian, late-Victorian, and fin de siècle lyric poetics are represented in a unique material and culturally specific form. By radically abridging the collected writings of Johnson and distilling them into a marketable form, Mathews constructs particular ways of reading the poetry book of the fin de siècle and of creating a poetry book that could function as a seductive short encounter for the reader. This essay explores the critical spirit informing the posthumous editions of Johnson’s poetic works and how such key figures of the period as Mathews, Yeats, and Pound articulated their critical revisions of fin de siècle poetic practices through the selective editing of Johnson’s complex poetic style. This essay argues that this kind of strategic revision of late-Victorian lyricism, decoration, and ritualized poetics does not merely function in relation to decorative publishing practices of the fin de siècle or as a denial of Johnson’s aesthetic sensibilities but that it points to a broader cultural criticism of Victorian aesthetic excess and of mid- to late-Victorian aesthetic ideology.